THE SANDF AS A HUMAN SECURITY INSTRUMENT POST-1994 (The Strategic Review for Southern Africa, 2020)
South Africa adopted a human security orientation at the start of its democratic epoch in 1994, but its operationalisation by the South African National Defence Force (SANDF) proved difficult to implement. Human security is an approach to security which prioritises the protection of the people over security of the state. One of its central tenets is that security is best achieved through development as opposed to arms. Against this backdrop, the principal objective of this article is to critically analyse and understand South Africa's official human security orientation. Two indicators, the functions performed by the SANDF as well as South Africa's strategic defence posture, were assessed to achieve the objective. The securitisation model associated with Barry Buzan and Ole Wæver was used as a theoretical framework to understand South Africa's official conception and utilisation of human security. It was found that the SANDF's operational functioning was compromised by having to perform its primary responsibilities along with secondary developmental tasks demanded by the broad mandate of human security. Furthermore, while South Africa lexically took human security and state security to be equally important, in practice the SANDF tended to prioritise state security ahead of human security both at home and abroad. Some analysts detected lack of strategic coherence in South Africa's security engagements in Africa while ignoring extensive efforts of the SANDF to bring peace, and not destabilisation, on the continent as part of the strategic defence posture. Ultimately, this article argues that the competency with which the SANDF ensures Strategic Review for Southern Africa, Vol 38, No 2 Thuso Benton Mongwaketse  29 state security must be cascaded down to the human level by taking up more secondary functions with some provisos. Alignment of defence policy and adequate resources as well as the involvement of the people will be indispensable towards realisation of true human security.